Kegiatan Pengabdian Masyarakat Terhadap Deteksi Dini Gangguan Perilaku, Emosional, dan Psikososial Di Sekolah Dasar Panyaweuyan - Fransisca Iriani R Dewi; Nivia Nivia; Putri Oktariana; Juniven Claudes; Monica Glory Faithtria; Bayu Eko Saputro; Mochamad Hammam Tegar Utomo; Alexander Halim Santoso (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this community service activity is to provide early detection of behavioral, emotional and psychosocial disorders in elementary school children using the questionnaire filling method. In this activity, interviews were conducted with students regarding the pediatric symptom checklist 17 (PSC-17) questionnaire. It is hoped that it can increase students' insight and awareness, so that they can prevent negative impacts resulting from behavioral, emotional and psychosocial disorders in the future.